Biochar addition can negatively affect plant community performance when altering soil properties in saline-alkali wetlands - Wang, Ziyi; He, Mengxuan; Lu, Xueqiang; Meng, Zirui; Liu, Jie; Mo, Xunqiang (Frontiers in Plant Science, 2024)
Biochar is a widely proposed solution for improving degraded soil in coastal wetland ecosystems. However, the impacts of biochar addition on the soil and plant communities in the wetland remains largely unknown. In this study, we conducted a greenhouse experiment using soil seed bank from a coastal saline-alkaline wetland. Three types of biochar, including Juglans regia biochar (JBC), Spartina alterniflora biochar (SBC) and Flaveria bidentis biochar (FBC), were added to the saline-alkaline soil at ratios of 1%, 3% and 5% (w/w). Our findings revealed that biochar addition significantly increased soil pH, and increased available potassium (AK) by 3.74% - 170.91%, while reduced soil salinity (expect for 3% SBC and 5%SBC) by 28.08% - 46.93%. Among the different biochar types, the application of 5% FBC was found to be the most effective in increasing nutrients and reducing salinity. Furthermore, biochar addition generally resulted in a decrease of 7.27% - 90.94% in species abundance, 17.26% - 61.21% in community height, 12.28% - 56.42% in stem diameter, 55.34% - 90.11% in total biomass and 29.22% - 78.55% in root tissue density (RTD). In particular, such negative effects was the worst in the SBC samples. However, 3% and 5% SBC increased specific root length (SRL) by 177.89% and 265.65%, and specific root surface area (SRSA) by 477.02% and 286.57%, respectively. The findings suggested that the plant community performance was primarily affected by soil pH, salinity and nutrients levels. Furthermore, biochar addition also influenced species diversity and functional diversity, ultimately affecting ecosystem stability. Therefore, it is important to consider the negative findings indirectly indicate the ecological risks associated with biochar addition in coastal salt-alkaline soils. Furthermore, Spartina alterniflora was needed to desalt before carbonization to prevent soil salinization when using S. alterniflora biochar, as it is a halophyte.